Managing for results : economic tasks and risk-taking decisions - Drucker, Peter F. (New York : Harper & Row, 1964)
This is a 'what to do' book. It deals with the economic tasks that any business has to discharge for economic performance and economic results. It attempts to organize these tasks so that executives can perform them systematically, purposefully, with understanding, and with reasonable probability of accomplishment.
Includes bibliographical references: p. 229-230.
uaa 21/01/2019
Loans
Keywords: Industrial management; Decision making; Management; Managerial economics; Risk